Where is Latin American Culture? From the Location of Culture to the Ethics of Culture - McClennen, Sophia A. (Revista Ciencia y Cultura, 2013)
Shifts in global power dynamics, structures of resistance, and critical approaches to thinking through the present indicate that it is time to vigorously confront the ethical questions at the heart of Latin American Cultural Studies as a first step in our theories and practice. This essay argues that a turn to ethics, especially one that derives from a critique of neoliberal biopolitics, reveals a need to move from an emphasis on the location of culture to the ethics of culture. The essay begins by tracing features of this newest phase in Latin American Cultural Studies. Whether we mark its shift along with John Beverley after 9/11 or whether we trace the current moment to the new millennium, it is clear that some of the critical categories that previously shaped the field no longer obtain in an era of globalization, neoliberal capitalism, and shifting notions of sovereignty. I then consider the role that ethics can play in reformulating the debates over identity politics, cultural rights, and struggles for recognition and redistribution. The third section turns to the overdetermined nature of cultural location and asks why location persists in framing so much of the critical discourse about globalization and culture. Despite the fact that much of the local versus global debate has been problematized and discredited, it remains the case that geographical framing of cultural origins continues to be one of the key dynamics at play, even if those frames are understood to be hybrid, glocal, or transterritorial.